Long‐term efficacy and tolerability of azilsartan medoxomil/chlorthalidone vs olmesartan medoxomil/hydrochlorothiazide in chronic kidney disease. Issue 4 (4th March 2018) - Bakris, George L.; Zhao, Lin; Kupfer, Stuart; Juhasz, Attila; Hisada, Michie; Lloyd, Eric; Oparil, Suzanne
Abstract : An open‐label, long‐term study evaluated safety and tolerability of azilsartan medoxomil/chlorthalidone (AZL‐M/CLD) vs olmesartan/hydrochlorothiazide (OLM/HCTZ) in hypertensive participants with stage 3 chronic kidney disease. Initial therapy was AZL‐M/CLD 20/12.5 mg (n = 77) or OLM/HCTZ 20/12.5 mg (n = 76), but could be up‐titrated (AZL‐M/CLD to 40/25 mg; OLM/HCTZ to 40/25 mg [US] or 20/25 mg [Europe]) with other agents added during weeks 4‐52. Primary endpoint was proportion of participants with ≥ 1 adverse event (AE) through week 52. Baseline demographics were similar. AEs did not differ between groups (88.3%, AZL‐M/CLD vs 76.3%, OLM/HCTZ; P  = .058). AZL‐M/CLD showed greater systolic BP reductions after initial dosing ( P  = .037) but not during long‐term follow‐up ( P  = .588). A greater proportion of participants up‐titrated to the highest dose with OLM/HCTZ (48.7%) vs AZL‐M/CLD (29.9%) ( P  = .021) and were taking additional antihypertensive medications (26.3% vs 16.9%). Both AZL‐M/CLD and OLM/HCTZ showed similar efficacy and tolerability.